Attitude of Rice Farmers Towards Utilization of Irrigation Technologies in Kogi State Nigeria - Olalekan, Oluwaseun Matina; Alfred, Simeon DadaYomi (Journal of Science, Technology and Innovation Research, 2025)
The study examined the attitudes of rice farmers towards utilization of irrigation technologies in Kogi State, Nigeria. The study employed a multi-stage sampling process to choose fifty-six respondents. The data collected for this study were analyzed using descriptive statistics including mean, percentage, and frequency. The participants were still in their prime working and active years, with larger percentage of them having one form of education or the other. The utilization of irrigation technologies by the farmers had improved food security, enhanced their capacity building and also encouraged them to invest more in agriculture. The study concluded that the respondents had positive towards the utilization of irrigation technologies